Implementación de un sistema contable de servicios para la asociación de comerciantes minoristas “Cotopaxi” del cantón La Maná período de enero al 30 de junio del 2008 - Espín Ortega, Bertha Elina (2012)
The services accounting within the development and change account process in the “COTOPAXI” Retailers Association, it is possible to state that these tools are used to perfect and lead toward the account and the accounting theory regulation, it is necessary to get a theoretical framework that hold its logical structure related to the administrative and financial accounting in order that the thesis research have some basic discernments, fitting the comprehension of the topic to be developed. During this project, it has been used the exploratory investigation which allowed to increase the investigator feasibility with the phenomenon to be investigated. With the considered methodological formulation it is looked to know the methodology that is going to be applied in the “COTOPAXI” Retailers Association. In order to control the commercial activities, to identify the mistakes in the accounting management and to open a change idea through the incorporation of an accounting control design, improving the commercial administration and therefore the management….